Performance Analysis of a Novel Directly Combined Organic Rankine Cycle and Dual-Evaporator Vapor Compression Refrigeration Cycle - Nagihan Bilir Sag; Metehan Isik (Applied Sciences)
Combining Organic Rankine Cycles (ORC) with cooling cycles offers a promising approach to achieving greater outputs within a single system. In this study, a novel directly combined ORC-VCC system has been designed to not only meet the cooling demand using a geothermal heat source but also generate power. The proposed novel ORC-VCC system has been analyzed for its energetic performance using four selected fluids: R290, R600a, R601, and R1234ze(E). Parametric analysis has been conducted to investigate the effects of parameters of heat source temperature, heat source mass flow rate, cooling capacities, condenser temperature, ORC evaporator temperature, pinch point temperature difference and isentropic efficiencies on net power production. Among the working fluids, R290 has provided the highest net power production under all conditions in which it was available to operate. Additionally, the results have been analyzed concerning a reference cycle for comparative evaluation. The proposed novel cycle has outperformed the reference cycle in all investigated cases in terms of net power production such as demonstrating an improvement of approximately from 8.7% to 57.8% in geothermal heat source temperature investigations. Similar improvements have been observed over the reference cycle at lower heat source mass flow rates, where net power increases by up to 50.8%.